2015
DOI: 10.1155/2015/593075
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immunity and Antigen‐Specific Activation in Obesity‐Associated Insulin Resistance

Abstract: Type 2 diabetes mellitus (T2D) is a metabolic disease that is strongly tied to obesity and often preceded by insulin resistance (IR). It has been established that chronic inflammation of hypertrophic adipose tissue depots in obese individuals leads to obesity-associated IR and is mediated by cells of the innate immune system, particularly macrophages. More recently, cells of the adaptive immune system, B and T lymphocytes, have also emerged as important regulators of glucose homeostasis, raising the intriguing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 149 publications
2
20
0
Order By: Relevance
“…Recent reports have shown that the infiltration of CD8+ T cells precedes M1‐polarized macrophage recruitment, and the interactions between T cells and macrophages are considered to constitute a maladaptive feed‐forward loop, which leads to adipose inflammation and insulin resistance . We also observed that PF4178903 specifically reduced the accumulation of CD8+ T cells but did not influence CD4+ T cells in adipose tissue (Figure D‐F).…”
Section: Discussionsupporting
confidence: 59%
“…Recent reports have shown that the infiltration of CD8+ T cells precedes M1‐polarized macrophage recruitment, and the interactions between T cells and macrophages are considered to constitute a maladaptive feed‐forward loop, which leads to adipose inflammation and insulin resistance . We also observed that PF4178903 specifically reduced the accumulation of CD8+ T cells but did not influence CD4+ T cells in adipose tissue (Figure D‐F).…”
Section: Discussionsupporting
confidence: 59%
“…Type 2 diabetes mellitus (T2DM) afflicts ∼387 million people worldwide and has become a major threat to public health. [ 1 ] Features of T2DM include insulin resistance and pancreatic β-cell dysfunction. [ 2 , 3 ] The accumulation of fat in the liver and excessive accumulation of visceral adipose tissue are reported risk factors for insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Like the cells of innate immunity, orchestration of immune responses by cells of adaptive immunity determines the metabolism and biology of AT. IR is associated with increases in cell populations with a pro-inflammatory phenotype including Th1, Th17, CD8+ cytotoxic T cells, and B-2 over those cell populations with regulatory properties mainly Treg and B-1a [66]. IFNγ and IL-17 secreted by Th1 and Th17 cells, respectively activate the pro-inflammatory functions of macrophages through the release of TNF-α, IL-6, and IL-1.…”
Section: Cells Of Adaptive Immunitymentioning
confidence: 99%